2013
DOI: 10.3989/mc.2013.04712
|View full text |Cite
|
Sign up to set email alerts
|

Ceniza de cascarilla de arroz como fuente de sílice en sistemas cementicios de ceniza volante y escoria activados alcalinamente

Abstract: This study assesses the viability of using an agro-industrial by-product, rice husk ash (RHA) from a Colombian rice company's combustion facility, as a total replacement for the commercial sodium silicate ordinarily used in alkaliactivated binders. Fly ash (FA), granulated blast furnace slag (GBFS) and binary 50FA:50GBFS blended pastes were activated with a mix of sodium hydroxide and either sodium silicate or one of two types of RHA. The pastes were characterised for strength, mineralogy and microstructure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
3
19
0
2
Order By: Relevance
“…Prior studies have shown that the co-precipitation of these two gels in hybrid cements is possible (38)(39)(40)(41)(42)(43)(44)(45)(46), although recent research has revealed that the two products do not develop singly as two separate gels, but that they interact, undergoing structural and compositional change in the process (104).…”
Section: Co-precipitation Of Cementitious Gels: C-s-h + N-a-s-hmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that the co-precipitation of these two gels in hybrid cements is possible (38)(39)(40)(41)(42)(43)(44)(45)(46), although recent research has revealed that the two products do not develop singly as two separate gels, but that they interact, undergoing structural and compositional change in the process (104).…”
Section: Co-precipitation Of Cementitious Gels: C-s-h + N-a-s-hmentioning
confidence: 99%
“…Procedure 3: today, a mixed alkaline activation procedure, a combination of the preceding two, can also be described. The product in this case is a new type of binder known as a hybrid alkaline cement, formed as the result of the alkaline activation of materials with CaO, SiO 2 and Al 2 O 3 contents >20% (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Alkali-activated Cementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adicionalmente, se emplean técnicas de análisis como la Difracción de Rayos X (DRX) y el Microscopio Electrónico de Barrido (MEB) [20][21][22][23], para conocer la composición mineralógica y morfología de la ceniza, el cemento utilizado y los especímenes fabricados para los diferentes tipos de ensayos a compresión, flexión y tracción indirecta.…”
Section: Introductionunclassified
“…The production of commercial silicate solutions (Na 2 SiO 3 ·nH 2 O and K 2 SiO 3 ·nH 2 O) involves a high energy demand (temperatures close to 1000 °C-1400 °C) and the emission of greenhouse gases (7,8). In recent years there has been great interest for the use of alternative sources of amorphous reactive silica for producing alkaline activators: rice husk ash (3,4,(9)(10)(11)(12)(13)(14)(15)(16)(17), silica fume (2,3,(18)(19)(20)(21) and waste glasses (1,(22)(23)(24)(25) have been used and have shown similar microstructure and mechanical performance to geopolymers produced with commercial soluble silicate solutions (3,9,18,26,27).…”
Section: Introductionmentioning
confidence: 99%